Strategic alliances between communities, with special reference to the twinning of South African provinces, cities and towns with international partners - De Villiers, J. C. (Jacobus Christiaan) (Stellenbosch : University of Stellenbosch, 2011)
Dissertation (PhD)--University of Stellenbosch, 2005.